"We Are Already Sick": Infectious Waste Management and Inequality in the Time of Covid-19, a Reflection from Blantyre, Malawi. Issue 1 (24th June 2020) - Tilley, Elizabeth; Kalina, Marc
The efficient and sanitary management of infectious waste is an essential part of the humanitarian response to any disaster, including the ongoing Covid-19 pandemic. Unfortunately, in many contexts within the Global South, waste management systems are poorly equipped to handle these waste streams during periods of normalcy, let alone during times of crisis. The purpose of this article is draw attention to a number of existing inequalities that define infectious waste management practices globally, with a critical eye to how they constrain poorer nations' ability to respond and manage their own Covid-19 outbreaks. In particular, the work draws on the authors' extensive research, experience, and activism at Queen Elizabeth Central Hospital in Blantyre, Malawi, to understand how waste management practices will inform and react to mitigation efforts and to propose a number of practical steps that can be achieved in the short-term, as well as towards long-term structural transformation. Ultimately, this conversation is meant to contribute to a more inclusive and critical waste management studies discourse.